Phenylpyruvic Acid-2-O-β-D-Glucoside Attenuates High Glucose-Induced Apoptosis in H9c2 Cardiomyocytes - Dludla, Phiwayinkosi Vusi; Muller, Christo John Frederick; Joubert, Elizabeth; Louw, Johan; Gabuza, Kwazi Bethuel; Huisamen, Barbara; Essop, M. Faadiel; Johnson, Rabia (Planta Medica, 2016)
Chronic hyperglycemia is closely associated with impaired substrate metabolism, dysregulated mitochondrial membrane potential, and apoptosis in the diabetic heart. As adult cardiomyocytes display a limited capacity to regenerate following an insult, it is essential to protect the myocardium against the detrimental effects of chronic hyperglycemia. This study therefore investigated whether phenylpyruvic acid-2-O-β-D-glucoside, present in Aspalathus linearis (rooibos), is able to attenuate hyperglycemia-induced damage in H9c2 cardiomyocytes. H9c2 cardiomyocytes were exposed to a high glucose concentration (33 mM) prior to treatment with phenylpyruvic acid-2-O-β-D-glucoside (1 µM), metformin (1 µM), or a combination of phenylpyruvic acid-2-O-β-D-glucoside and metformin (both at 1 µM). Our data revealed that high glucose exposure increased cardiac free fatty acid uptake and oxidation, mitochondrial membrane potential, and apoptosis (caspase 3/7 activity and TUNEL), and decreased the Bcl2/Bax protein expression ratio. Phenylpyruvic acid-2-O-β-D-glucoside treatment, alone or in combination with metformin, attenuated these glucose-induced perturbations, confirming its protective effect in H9c2 cardiomyocytes exposed to chronic hyperglycemia.
Keywords: phenylpyruvic acid-2-O-β-D-glucoside; hyperglycemia; fatty acid uptake and oxidation; myocardial apoptosis